Adoption Level of Good Aquaculture Practices in Brackish Water Pond Aquaculture, Pinrang Regency, South Sulawesi Province - Akhmad Mustafa; Admi Athirah; Erna Ratnawati; Ruzkiah Asaf; Tarunamulia Tarunamulia (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Pinrang Regency is a center of brackish water pond aquaculture production in South Sulawesi Province in which some of brackish water pond farmers in this regency have adopted Good Aquaculture Practices (GAqP). A study was conducted to determine GAqP adoption level, to identify GAqP aspects required to be improved, and to determine the category of GAqP adoption level as the first step to maximize the GAqP adoption level in the brackish water ponds. Primary data were obtained from 76 respondents consisted of pond farmers who already have adopted and or obtained GAqP certificates. On the basis of the adoption level, the adoption level classification is carried out into three categories, namely low adopters, medium adopters, and high adopters. The results showed that the highest GAqP adoption levels in brackish water ponds were in food security (89.41%) and technical aspects (78.57%). The lowest GAqP adoption levels were in management (8.71%) and environmental aspects (0%). It was also reported that the GAqP adoption level in brackish water ponds varied from 40.58 to 67.01% with an average of 42.86% and was categorized as moderate adopters. Based on this study, management and environmental aspects were found to be the aspects that need serious attention to increase the GAqP adoption level in the brackish water ponds.